Mothers' challenges and experiences of children with cerebral palsy: a qualitative meta-synthesis - Peng Meng-Yun; Lu Yi-Fu (Sciendo, 2024)
To examine what challenges and experiences a mother faces in caring for children with cerebral palsy (CP). As the main caregiver of children with CP, mothers are under multiple pressures. Even though mothers' challenges and experiences of children with CP will affect their quality of life and the rehabilitation of the children, little is known about their challenges and experiences during the whole care.